2012
DOI: 10.1007/s00221-012-3079-7
|View full text |Cite
|
Sign up to set email alerts
|

Ventral and dorsal fiber systems for imagined and executed movement

Abstract: Although motor imagery is an entirely cognitive process, it shows remarkable similarity to overt movement in behavioral and physiological studies. In concordance, brain imaging studies reported shared fronto-parietal sensorimotor networks commonly engaged by both tasks. However, differences in prefrontal and parietal regions point toward additional cognitive mechanisms in the context of imagery. Within the perspective of a general dichotomization into dorsal and ventral processing streams in the brain, the que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(53 citation statements)
references
References 111 publications
5
48
0
Order By: Relevance
“…The present interpretation of the data by no means excludes the possibility of a cross-talk between bottom-up and top-down processes, which are known to influence each other at several levels of response processing. This datum actually fits well with models proposed in nonhuman primates (Boussaoud et al 1995;Lebedev and Wise 2002) and in humans Toni, Rushworth, et al 2001;Vry et al 2012) describing 2 routes to action that rely on the dorsal and the ventral visual streams. An additional dissociated effect of rTMS over the 2 target areas is that parietal stimulation produced an effect on the representation of the congruent movement, that is, on the movement that was seen in the visual stimulus and, on the contrary, prefrontal stimulation produced an effect limited to the incongruent movement, that is, to the movement that was NOT seen in the visual stimulus but that had to be implemented in the countermirror task.…”
Section: Discussionsupporting
confidence: 71%
“…The present interpretation of the data by no means excludes the possibility of a cross-talk between bottom-up and top-down processes, which are known to influence each other at several levels of response processing. This datum actually fits well with models proposed in nonhuman primates (Boussaoud et al 1995;Lebedev and Wise 2002) and in humans Toni, Rushworth, et al 2001;Vry et al 2012) describing 2 routes to action that rely on the dorsal and the ventral visual streams. An additional dissociated effect of rTMS over the 2 target areas is that parietal stimulation produced an effect on the representation of the congruent movement, that is, on the movement that was seen in the visual stimulus and, on the contrary, prefrontal stimulation produced an effect limited to the incongruent movement, that is, to the movement that was NOT seen in the visual stimulus but that had to be implemented in the countermirror task.…”
Section: Discussionsupporting
confidence: 71%
“…So far, there are several data supporting that MI and physical practice share the same neural substrate, although there are also some differences within the pattern of activity in these areas (Hetu et al, 2013). Notably, Lacourse, Turner, Randolph-Orr, Schandler, and Cohen (2004) reported that MI training was accompanied by an increased activation of M1, but to a lesser extent compared to physical practice, while Vry et al (2012) found that the DLPFC and the parietal cortex are anatomically connected and more activated during MI than actual execution. Based on these findings, we may hypothesize that during constant MI practice, M1 activation might be less important than that of the DLPFC during variable practice, and this ''unbalancedactivation'' could, therefore, be effective in the motor output following a consolidation period that includes a night of sleep.…”
Section: Discussionmentioning
confidence: 88%
“…From this, it follows that the interhemispheric transmission is fastest and most efficient in this area which is capable of transmitting reliable, precisely timed neuronal coupling. Hence, it is plausible that the frequency-specific interhemispheric correlation structure of spontaneous oscillatory neuronal activity is nested in the highest frequency range (32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45) between the sensorimotor cortices compared to the temporal lobes (4-6 Hz) and the lateral parietal areas (8-23 Hz) [58]. Large-diameter axon fibers may also determine the degree of interhemisphericcorrelated fMRI resting-state activity which is again highest in the somatosensory cortices [59].…”
Section: Dti-the Left Dorsal Stream and Interhemispheric Somatosensormentioning
confidence: 99%
“…The key to fluent speech is a production-perception interaction. The timely sequencing and context-dependent binding of speech units are constantly monitored and adjusted by an effective sensorimotor integration [39]. Feedback-related control couples not only perception and production processes but also internal models that closely relate to the sound envelop of a corresponding utterance [40] possibly translating auditory targets into motor commands.…”
Section: The Continuous Speech Streammentioning
confidence: 99%